2003
DOI: 10.1037/0894-4105.17.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive complaints, depression, medical symptoms, and their association with neuropsychological functioning in HIV infection: A structural equation model analysis.

Abstract: The main objective of this study was to use structural equation modeling (SEM) to clarify the relationship between subjective cognitive complaints and neuropsychological functioning in 160 adults with HIV infection. Participants completed questionnaires assessing cognitive complaints, symptoms of depression, and HIV-related medical symptoms. Neuropsychological tests included measures of attention, verbal fluency, psychomotor skills, learning, memory, and executive skills. SEM was used to test models of the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(64 citation statements)
references
References 62 publications
(79 reference statements)
9
55
0
Order By: Relevance
“…In contrast, depressive complaints were strongly associated with self-report of neurobehavioral problems in both countries. This finding also is consistent with what has been reported in North American HIV cohorts (Carter et al, 2003;Rourke et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, depressive complaints were strongly associated with self-report of neurobehavioral problems in both countries. This finding also is consistent with what has been reported in North American HIV cohorts (Carter et al, 2003;Rourke et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…It is unclear whether NP impairment still produces worse medical outcomes in the context of HAART, but there is considerable evidence that even mild NP impairment is associated with reduced vocational functioning and other difficulties with cognitive aspects of everyday functioning: medication management, driving, and Instrumental Activities of Daily Living (IADLs; Carter et al, 2003;Heaton et al, 2004a;Hinkin et al, 2004;Marcotte et al, 2006). It is unknown whether any NP deficits that may be observed among HIV infected Chinese farmers would have the same relevance in their lives, or if such deficits could even be noticed by the patients and others around them.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed discordance between self-reported cognitive functioning and objective indices of neuropsychological performance has been documented among HIVinfected individuals [95]. However, other research has found increased cognitive complaints to predict poorer neuropsychological test performance and thus supports a relation between self-reported cognitive complaints and neuropsychological skills among HIV-infected individuals [52]. Further, the majority of observed cognitive impairment among HIV-infected individuals in the post-ART era is mild, variable, and may go undetected (asymptomatic neurocognitive impairment, mild neurocognitive disorder [see 27]).…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, the ecological validity of using neuropsychological tests to assess cognitive function having been questioned [48] due to the nature of laboratory settings for neuropsychological testing, the potential for interactive effects of increased demands on cognition in everyday settings and cognitive deficits, and compensatory strategies that may be effective for a laboratory-based task (e.g., Modified Wisconsin Card Sorting Task) but are not reflected in selfreported memory skills [49]. Although neuropsychological tests provide objective data for specific cognitive deficits, it has been argued that subjective cognitive measures are more sensitive indices for everyday memory functioning [see 50,51], such as patients' experience of everyday memory failures or milder, more variable cognitive struggles that fluctuate over time [e.g., [52][53][54]. Use of selfreport measures (i.e., meta-memory) may therefore provide a complimentary lens through which to examine the effects of problematic alcohol use on memory functioning among individuals with HIV.…”
Section: Introductionmentioning
confidence: 99%